ESTUDIO DE LA REGENERACION DE LOS SABINARES DE SABINA ALBAR (JUNIPERUS THURIFERA L.) EN LA PROVINCIA DE ALBACETE (Congreso Forestal Español, Lourizán - Pontevedra. 1993, 1993)
61 plots selected using photographs were studies in one Juniperus thurifera forest located in the W of the Albacete Province (SE Spain). In each plot, the regeneration of this species was measured considering a key of three patems of regeneration. Also, sorne ecological factors linked to this process were also measured. A very high regeneration was pro ved in those plots that represented forests of J. thurifera and Quercus rotundifolia highly mixed. In those plots with only individual s of J. thurifera there was a minor regeneration of this species. A better protection against livestock, edaphic moisture, and luminosity conditions can be adduced as sorne causes of this difference in the regeneration.